2021
DOI: 10.1016/j.socscimed.2021.114333
|View full text |Cite
|
Sign up to set email alerts
|

Health behaviors and mental health during the COVID-19 pandemic: A longitudinal population-based survey in Germany

Abstract: Objective To understand the mental health response to repeated and prolonged stress during the COVID-19 related lockdown and the role of specific health behaviors to buffer against this stress. Methods In a longitudinal study with several measurement points covering three months during the COVID-19 pandemic, about 3500 randomly selected participants representative of the German population reported on their mental health (anxiety, depression, loneliness) and health behav… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

13
80
1
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 100 publications
(102 citation statements)
references
References 55 publications
13
80
1
2
Order By: Relevance
“…Interestingly, in our sample, well-being was not related to PA. This is in line with the large Mannheim Corona Study [35] but in contrast to the aforementioned study in German students [33]. Investigations from the first wave of the pandemic also found positive associations between PA and well-being [36,37].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…Interestingly, in our sample, well-being was not related to PA. This is in line with the large Mannheim Corona Study [35] but in contrast to the aforementioned study in German students [33]. Investigations from the first wave of the pandemic also found positive associations between PA and well-being [36,37].…”
Section: Discussionsupporting
confidence: 82%
“…Based on our data, we cannot say whether PA has reverted to normal levels between the lockdowns. In the Mannheim Corona Study, PA levels in the overall sample surpassed pre-lockdown values in June 2020 (i.e., after the lifting of the restrictions), but certain groups, such as women, parents and people with compromised health, were less active [35]. In Canada, moderate-vigorous PA returned to pre-lockdown levels after the first wave; incidental PA and walking, however, remained significantly lower [38].…”
Section: Discussionmentioning
confidence: 95%
“…We found that depression and anxiety decreased over the 3-month follow-up period and was consistent for all demographic subgoups. In a German cohort over roughly the same time period (April to June 2020) as our study, Mata et al also noted a decline in anxiety and depression ( Mata et al, 2021 ). We do not know what may explain these results, although it is possible that respondents were adapting to the lockdown.…”
Section: Discussionsupporting
confidence: 79%
“…We do not know what may explain these results, although it is possible that respondents were adapting to the lockdown. Mata et al hypothesized habituation to stay at home orders would result in improved mental health symptoms ( Mata et al, 2021 ). We noted that prevalence of lockdown behaviors decreased somewhat over these months, which may have improved the respondents' mental health outlook.…”
Section: Discussionmentioning
confidence: 99%
“…This finding may contradict the evidence that PWE are sensitive to a dramatic social change due to the pandemic [ 9 ]. However, even if PWE had a psychological risk, we considered that they could have gradually adapted to ongoing social change and the new normal lifestyle [ 27 ]. Such habituation might be key for PWE during the long-term chronological change in the pandemic.…”
Section: Discussionmentioning
confidence: 99%